2022
DOI: 10.1002/acr.24588
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Baseline Meniscal Symptoms and Outcomes of Operative and Nonoperative Treatment of Meniscal Tear in Patients With Osteoarthritis

Abstract: Objective. Patients with meniscal tears reporting meniscal symptoms such as catching or locking have traditionally undergone arthroscopy. The present study was undertaken to investigate whether patients with meniscal tears who report meniscal symptoms have greater improvement with arthroscopic partial meniscectomy (APM) than physical therapy (PT).Methods. We used data from the Meniscal Tear in Osteoarthritis Research (MeTeOR) trial, which randomized participants with knee osteoarthritis (OA) and meniscal tear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Routine use of an MRI for diagnosis of degenerative knee disease is not recommended for this specific patient group due to the poor association with symptoms [ 13 , 20 , 21 , 32 ]. Similarly, arthroscopic interventions are not recommended for routine use in degenerative knee disease because limited benefits are found that are absent 1 to 2 years after surgery [ 16 , 27 , 28 , 39 , 40 , 43 ]. Only when locking symptoms are present, a knee arthroscopy may be warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Routine use of an MRI for diagnosis of degenerative knee disease is not recommended for this specific patient group due to the poor association with symptoms [ 13 , 20 , 21 , 32 ]. Similarly, arthroscopic interventions are not recommended for routine use in degenerative knee disease because limited benefits are found that are absent 1 to 2 years after surgery [ 16 , 27 , 28 , 39 , 40 , 43 ]. Only when locking symptoms are present, a knee arthroscopy may be warranted.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, no clinical study supports the proposition that occurrence of DMT would result in knee pain or that DMT is a defined independent clinical entity. In fact, clinical studies show that development of knee pain is not associated with the development of DMT and that “meniscal symptoms” are merely a correlate for cartilage damage (Bhattacharyya et al 2003 , Englund et al 2007 , Hare et al 2017 , MacFarlane et al 2021 ).…”
Section: Disease Framework: Can We Explain Pain?mentioning
confidence: 99%
“…Results were consistent at 5-year follow-up . While certain subgroups of patients may benefit from partial meniscectomy, often thought to be those with mechanical symptoms, secondary analyses from RCTs demonstrate that the presence of mechanical symptoms was not associated with improved pain relief …”
Section: Meniscal Tearsmentioning
confidence: 75%